(untitled) (REMUNOM, 2025)
Objective: To describe the managerial competency profile of nursing professionals in healthcare services. Methods: This is a Scoping Review. The review question is: What are the managerial competencies of nursing professionals in healthcare services? Studies related to the PCC mnemonic will be considered. The time frame will not be applicable. The studies will be written in English, Spanish, and Portuguese. They will be conducted only in hospital settings and Basic Health Units (UBS). The search strategy involved a preliminary search of Medline (PubMed) and Web of Science databases. The study selection process will be guided by the PRISMA (Extension for Scoping Reviews) flowchart, identifying and excluding studies through the Qatar Computing Research Institute (Rayyan QCRI) platform. Data extraction will be performed by the researchers, aiming to answer the guiding question of this scoping review. Evidence analysis and presentation of results will be evaluated based on content analysis, systematically structured and presented through publications and conferences. Partial considerations:The study expects that the expected results will lead to significant measures to strengthen management practices, leadership, people development, decision-making, and improvements in organizational culture.